Expression profile of Toll‐like receptor 4 in rat testis and epididymis throughout postnatal development - Özbek, Mehmet; Hitit, Mustafa; Ergün, Emel; Ergün, Levent; Beyaz, Feyzullah; Erhan, Füsun; Yıldırım, Nuh; Kandil, Banu; Özgenç, Özge; Memili, Erdoğan (Hindawi Limited, 2020)
Toll-like receptors (TLRs) belonging to pattern recognition receptors are involved in maintaining testicular and epididymal immune homeostasis. The purpose of the current study was to investigate TLR4 expression in rat testis and epididymis throughout postnatal development. Weak staining was detected in peritubular myoid cells and immature Sertoli cells while no staining was observed in gonocytes during prepubertal period. However, TLR4 expression began to appear in spermatocytes in pubertal period and gradually increased in spermatids. An intense staining was observed in steps 5-19 spermatids in post pubertal and mature periods. Similarly, TLR4 expression in the testes steadily increased from pubertal period to mature period. Puberty also caused a significant increase in TLR4 expression in epididymis. TLR4 expression in cauda epididymis was lower as compared to those of other epididymal segments. The majority of epididymal epithelial cells exhibited apical TLR4 expression, whereas basal cells showed intense intracytoplasmic immunoreaction. We detected an intense staining in epididymal smooth muscle cells. The expression levels of TLR4 showed dynamic changes in both spermatogenic cells, and entire testicular and epididymal tissues during postnatal development. These results suggest that TLR4 expression contributes not only to inflammation but also to the development of spermatogenic cells.
Keywords: Epididymis; Male; Myocytes, Smooth Muscle; Epithelial Cells; Immunohistochemistry; Spermatids; Rats; Toll-Like Receptor 4; Spermatocytes; Models, Animal; Testis; Animals; Sexual Maturation